Does caffeine supplementation improve physical performance of elite ice hockey players? A randomized, double-blind, placebo-controlled, counterbalanced, cross-over trial - Lozano-Berges, G., Pantoja, P., Moradell, A., Matute-Llorente, A., & Gomez-Bruton, A. (Science & Sports, 2023)
Objectives Although the positive effects of caffeine supplementation on individual and team-sports have been widely described, the literature evaluating the effect of caffeine supplementation on athletic performance in ice hockey players is almost non-existent. Therefore, the aim of the present study was to evaluate the effect of acute caffeine ingestion (3 mg/kg body mass).